SMARCB1 (INI1) retained but SMARCA4 (BRG1) negative atypical teratoid/rhabdoid tumor arising at the bilateral cerebellopontine angles: a case report. Issue 9 (30th September 2021) - Mitsui, Nobuyuki; Oikawa, Kensuke; Tanino, Mishie; Kinoshita, Manabu
Abstract: Most atypical teratoid/rhabdoid tumor (AT/RT) of the central nervous system shows an inactivation of SMARCB1 (INI1) and is considered as the hallmark of this neoplasm. However, AT/RT could exceptionally rarely present retained SMARCB1 (INI1) but inactivated SMARCA4 (BRG1). Here, the authors report a rare case of a 2-year-old boy with a SMARCB1 (INI1) retained but SMARCA4 (BRG1) negative AT/RT arising at the bilateral cerebellopontine angles mimicking neurofibromatosis type 2. The tumor was highly aggressive and was refractory to all treatment modalities. This case highlights the challenges during differential diagnosis of atypical cerebellopontine angle tumors of childhood and the importance of thoroughly investigating SMARCB1 (INI1) and SMARCA4 (BRG1) when AT/RT is suspected.